Implementation Permendag 31/2023 to Prohibition Social-Commerce on the Income of MSEs in Kota Ambon - Sandy Hukunala; Retsky Timisela (Warmadewa Press, 2024)
Social The background of this research sees that the phenomenon of social commerce, especially TikTok Shop, has become an online trade trend that attracts many MSEs. However, the presence of TikTok Shop also raises concerns about unfair business competition, shopping addiction, and lack of regulation and quality control. The object of this research is how the existence of Permendag 31/2023 issued by the government regarding the ban on social-commerce such as TikTok Shop affects the income of MSEs in Ambon Ciy. The research method used is empirical law with a legislative and sociology approach, using document studies, observations, surveys, and interviews. The results of the study show that the majority of MSE actors in Ambon City are not aware of the existence of this regulation, and only a few have experienced a decrease in income due to its implementation. Responses to these regulations have been mixed; The majority declined because they wanted to try out social trading platforms, while some supported the regulation to protect their business continuity. The conclusion of this research is that the implementation of Permendag 31/2003 faces significant challenges in terms of socialization and acceptance among MSE actors in Ambon City. The low knowledge of these regulations indicates the need for further efforts from the government to increase the understanding of MSE actors about the policies implemented.